Pemberdayaan Kader Kesehatan dalam Meningkatkan Kualitas Hidup Lansia dengan Inkontinensia Urine - Rustiana Kusumawati, Yoni; Utomo, Budi; Setiawan, Setiawan (Jurnal Empathy Pengabdian Kepada Masyarakat, 2024)
Background: Ageing that occurs in the elderly causes a decrease in pelvic floor muscle strength, which causes elderly people to become unable to control their urination activities, causing the elderly to suffer from urinary incontinence. Exercises to treat urinary incontinence include pelvic floor muscle exercises called Kegel exercises. A Kegel workout is a pelvic floor muscle exercise by contracting and relaxing the pelvic floor muscles. Kegel exercise to improve conditions resulting from decreased muscle function and strengthen the pelvic floor muscles Methods: Education about the quality of life of elderly people suffering from urinary incontinence. (2) Kegel exercise training and practice for health cadres; (3) Services by empowering community cadres to improve the quality of life of elderly sufferers of urinary incontinence. Results: There is an increase in the understanding and skills of health cadres in improving the quality of life of elderly people suffering from urinary incontinence and improving the quality of public health. Conclusion: Urinary incontinence with Kegel exercises has been proven to increase pelvic floor muscle strength and reduce the incidence of urinary incontinence in the elderly. The quality of life of the elderly increases and the frequency of daily urination decreases after Kegel exercises are given regularly. Health education activities and Kegel exercises must be carried out regularly so that they can provide health and preventive benefits for the elderly, both those who have or have not experienced urinary incontinence problems.